Natural fractures and discontinuities in a Lower Cretaceous chalk-marlstone reservoir, Valdemar Field, Danish North Sea. (February 2022) - Glad, Aslaug C.; Amour, Frédéric; Welch, Michael J.; Clausen, Ole R.; Anderskouv, Kresten; Ineson, Jon R.; Sheldon, Emma; Nick, Hamidreza M.
Abstract: Natural fractures and discontinuities have significant impact on subsurface flow conditions and thus production, of carbonate reservoirs, particularly in low-permeability sediments such as chalk-marl successions characterizing the Lower Cretaceous reservoirs in the Danish North Sea. Yet the diversity and distribution of the fractures are often poorly understood and largely underestimated. In heterogeneous, tight carbonate reservoirs, natural fractures can enhance permeability, as well as create secondary porosity and promote connectivity between reservoir compartments. The Valdemar Field, Danish Central Graben, represents the only producing field from the Lower Cretaceous in the Danish sector of the North Sea. The main reservoirs are confined to the Tuxen and Sola Formations. A new reservoir zonation is proposed based on facies characteristics and fracture patterns to consist of the lower Tuxen, middle-upper Tuxen, lower-middle Sola and upper Sola units with the Munk Marl Bed and Fischshiefer Member forming major reservoir barriers between the lower and the middle-upper Tuxen, and the lower-middle and the upper Sola units, respectively. The reservoir intervals are of heterogeneous nature and composed of interbeds of five main facies comprising chalk, slightly marly chalk, marly chalk, chalky marlstone and marlstone. Six types of natural fractures and discontinuities are identified in the Valdemar Field based on core studies: cemented fractures, deformation bands, open fractures with plumose structures and hackle marks, shear fractures, small-offset shear fractures and rubble zones. The most dominant fracture type within all facies is the open fractures with plumose structure and hackle marks followed by small-offset shear fractures, shear fractures and rubble zones. Cemented fractures and deformation bands are less dominant. The small-offset shear fractures, shear fractures and open fractures with plumose structures and hackle marks are flow enhancing, while the cemented fractures and deformation bands are neutral or flow reducing. Rubble zones are also recorded throughout the core material. If these represent naturally fractured zones, present under subsurface conditions, they would be strongly flow enhancing. The flow-enhancing natural fractures (open fractures, shear fractures and small offset shear fractures) have densities of 7.2/m in the chalk, 5.0/m in slightly marly chalk, 3.1/m in marly chalk, 4.8/m in the chalky marlstone while they are absent in the marlstone. The flow-enhancing fractures have densities of 4.6/m in the lower Tuxen reservoir, 4.0/m in the middle-upper Tuxen reservoir, 2.7/m in the lower-middle Sola reservoir, and 7.4/m in the upper Sola reservoir. This study provides a detailed analysis of the natural fractures and discontinuities occurring the Lower Cretaceous succession of the Danish North Sea Basin, and their relation to the sedimentary facies and reservoir units. Highlights: The Lower Cretaceous Valdemar Field of the Danish North Sea is a cyclically bedded chalk-marl reservoir. Four reservoir units are defined composed of different assemblages of five sedimentary facies varying from chalk to marl. Natural fractures and discontinuities occur frequent in all facies except marl with greater density in chalk-rich facies. Natural fractures are coupled to facies and reservoir units, being categorized as flow-enhancing, neutral or flow-reducing. Natural fractures, discontinuities and sedimentary facies have an impact on reservoir conditions, properties and fluid flow.